Collecting germplasm in Zimbabwe - Padulosi, S.; Ng, N.Q. (1989)
Reports the findings of a mission carried out by the International Institute of Tropical Agriculture in Zimbabwe to gather genetic resources of cowpea, rice, bambarra groundnut and their wild relatives. 461 samples of 365 species were collected. Sampling was made over 140 sites of both natural vegetation and cultivated habitats. The team was able to gather samples from farmers' stores (43%), markets (6%) and from standing crops 39%. 12% of the samples collected were from wild vegetation.